The Development of Renewable Energy Sources and its Significance for the Environment - Heshmati, Almas (Springer, 2015)
This book analyzes the effects of power generated by renewable energy sources, renewable energy production technologies, energy efficiency, and market regulation of carbon emissions. It elaborates on how these parameters have direct and indirect effects on carbon emission reduction, such as the results of an environmental tax that could directly reduce carbon emissions by decreasing fossil fuel consumption or by stimulating energy savings through technological innovation, as well as how renewable energy sources can affect both economic growth and the environment. In addition to a detailed analysis of the interrelationships between renewable energy consumption, production technology, and market regulation, The Development of Renewable Energy Sources and its Significance for the Environment proposes a model for measuring the effectiveness and results of the interaction between these links. Furthermore, a structure for a marketplace of renewable energy sources is put forward, as well as an outline of the requirements that must be met in order for this market to function. Suitable policy recommendations to enhance the market for renewable energies are also provided.